The Effect of Fraud Diamond on Detection of Financial Statement Fraud - Selly, Bambang Leo Handoko (International Journal of Advanced Science and Technology, 2020)
The purpose of this research is to analyze the influence of fraud diamond factors of financial target, external pressure, ineffective monitoring, and nature of industry, changes of external auditor, and changes in board of director on financial statement fraud. This research is conducted on mining companies listed in Indonesia Stock Exchange for the year 2014-2018. Total samples used in this research are 35 companies, determined by purposive sampling method. Data analysis used in this research is descriptive statistics test, multicollinearity, and logistic regression. The result of this research shows that independent variables of financial target, external pressure, ineffective monitoring, changes of external auditor, and changes in board of director do not affect financial statement fraud. Meanwhile, independent variable of nature of industry affects financial statement fraud